Will Cost-Effectiveness Decisions Determine Future 4D Air Traffic Management Concepts?. (7th November 2014) - Brooker, Peter
Abstract : Would an increased emphasis on cost-effectiveness and markedly reduced controller workload/costs determine the Four-Dimensional Air Traffic Management (4D ATM) Concept – a mindset change? Are there workable concepts that focus on flightpath conformance monitoring rather than a combination of conformance and hazard monitoring? Fundamental criteria for a conformance management-based system are identified to meet workload and cost goals. A 'Global Navigation Satellite System (GNSS)/Feedback Concept' is sketched, with radical ingredients to convert GNSS's accurate position fixes into accurate aircraft flightpath navigation. This eliminates air/ground trajectory synchronisation processing, and focuses conflict probing/planning tools on non-conforming flights. This concept would need to address key Human Factor concerns satisfactorily.